Thermal inactivation of actinidin as affected by meat matrix. (November 2018) - Zhu, Xiaojie; Kaur, Lovedeep; Boland, Mike
Abstract: Actinidin from kiwifruit can tenderise meat and add value to low-value meat cuts. However, as with other proteases, over-tenderisation of meat will occur if the reaction of actinidin is not controlled. We describe a process to control the enzyme activity by heat denaturation after the desired degree of meat tenderisation has been achieved. The thermal inactivation kinetics of actinidin in both fresh (KE) and commercial (CEE) green kiwifruit enzyme extract, were studied, with enzyme alone and with enzyme combined with homogenised meat. Both KE and CEE were inactivated at moderate sous vide temperatures (60 and 65 °C) in <5 min. However, the inactivation times increased considerably (up to 24 h at 60 and 65 °C) when these extracts were mixed with homogenised meat. The thermal inactivation kinetics in meat homogenates were used as a guide to optimise processing parameters for actinidin application to beef steaks, which will be described in a companion paper.